2021
DOI: 10.1177/15353702211006044
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and mechanism of fecal microbiota transplantation in mice with experimentally induced ulcerative colitis

Abstract: Restoring intestinal microbiota dysbiosis with fecal microbiota transplantation is considered as a promising treatment for ulcerative colitis. However, the mechanisms underlying its relieving effects remain unclear. Ulcerative colitis pathogenesis is associated with the involvement of immune cells and inflammatory cytokines. Here, we aimed to investigate the effect of fecal microbiota transplantation on T cell cytokines in a dextran sulfate sodium-induced ulcerative colitis mouse model. Five-aminosalicylic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Intestinal microbiota was restored to a compositional pattern close to that of the normal group following treatment with 5‐ASA, accompanied by a reduction in the level of intestinal inflammation. [ 46 ] However, the above results suggested that MBP can better regulate gut microbiota and reverse microbiota dysbiosis after DSS induction than 5‐ASA. Therefore, MBP might be performed by altering the composition of intestinal microorganisms to exhibit anti‐inflammatory and restorative functions of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 97%
“…Intestinal microbiota was restored to a compositional pattern close to that of the normal group following treatment with 5‐ASA, accompanied by a reduction in the level of intestinal inflammation. [ 46 ] However, the above results suggested that MBP can better regulate gut microbiota and reverse microbiota dysbiosis after DSS induction than 5‐ASA. Therefore, MBP might be performed by altering the composition of intestinal microorganisms to exhibit anti‐inflammatory and restorative functions of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 97%
“…FMT has been proven to be efficacious in treating IBD; however, its mechanism of action remains unclear. Recently, several researchers have focused on studying the (27) found that FMT controlled experimentally induced ulcerative colitis by improving T helper 1 (Th1)/T helper 2 (Th2) and T helper cell 17 (Th17)/regulatory cells (Treg) imbalance through the regulation of the intestinal microbiota. Another study suggested that FMT could increase the abundance of the gut bacteria that produce short-chain fatty acids, which in turn decreased proinflammatory cytokine production by suppressing the nuclear factor-kappa B signaling pathway (28).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that compared with spontaneous recovery without intervention treatment, FMT can help in the rapid recovery of mucosal permeability caused by dysbiosis [69] . In addition, for experimentally induced UC, FMT has been shown to lead to improved intestinal barrier integrity and reduction in colonic inflammation [70] . Therefore, FMT can be used to alleviate, treat, or prevent the occurrence and development of UC.…”
Section: Intestinal Bacteria Are Important Factors For the Development Of Uc And Dysbiosis Further Increases Susceptibility To Ucmentioning
confidence: 99%